2006
DOI: 10.4049/jimmunol.177.12.8456
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between T Cells Responding to Concurrent Mycobacterial and Influenza Infections

Abstract: CD4+ T cells are central in mediating granuloma formation and limiting growth and dissemination of mycobacterial infections. To determine whether T cells responding to influenza infection can interact with T cells responding to Mycobacterium bovis bacille Calmette-Guérin (BCG) infection and disrupt granuloma formation, we infected mice containing two monoclonal T cell populations specific for the model Ags pigeon cytochrome c (PCC) and hen egg lysozyme (HEL). These mice were chronically infected with PCC epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Mouse models have shown that prior exposure to influenza A impairs immune responses to Mtb infection and decreases survival (Redford et al 2014), possibly through down-regulated MHC (major histocompatibility complex) expression on dendritic cells and reduced activation of CD4 and CD8 T cells to clear mycobacteria (Florido et al 2013). A similar murine study found influenza had little effect on mycobacterial load (Co et al 2006). Clinical data from Southeast Asia does not support an association between influenza and TB (de Paus et al 2013;Noh et al 2013;Roth et al 2013).…”
Section: Influenzamentioning
confidence: 72%
“…Mouse models have shown that prior exposure to influenza A impairs immune responses to Mtb infection and decreases survival (Redford et al 2014), possibly through down-regulated MHC (major histocompatibility complex) expression on dendritic cells and reduced activation of CD4 and CD8 T cells to clear mycobacteria (Florido et al 2013). A similar murine study found influenza had little effect on mycobacterial load (Co et al 2006). Clinical data from Southeast Asia does not support an association between influenza and TB (de Paus et al 2013;Noh et al 2013;Roth et al 2013).…”
Section: Influenzamentioning
confidence: 72%
“…One possibility is a physical barrier at the surface of the structure. Findings from several studies have revealed that recently activated antigen-nonspecific T cells can enter established granulomas (Co et al, 2006;Hogan et al, 2007;Sewell et al, 2003), but given that in these previous studies T cells had the opportunity to enter the lesion over a relatively long time period (1 or more weeks), the permeability of the granuloma border was unclear. We found that T cells can enter granulomas within minutes of localizing to their borders and subsequently accumulate within these structures, displaying rapid motility, highly restricted migration, and limited egress into the surrounding sinusoidal space.…”
Section: Discussionmentioning
confidence: 97%
“…catheter. Because T cells can localize to granulomas in the absence of antigen recognition (Co et al, 2006), we hypothesized that these OTII-RAG cells would serve as a source of T cells with the potential to enter the granuloma. By using a fluorescent blood tracer to delineate the borders of individual granulomas, we observed a rapid recruitment of activated T cells into these structures beginning 20 min after T cell transfer, with increasing numbers of cells accumulating within the granuloma over the next 2 hr (Figures 6A and 6B; Movie S14).…”
Section: Exogenous Effector T Cells Are Rapidly Recruited Into and Rementioning
confidence: 99%
“…Coinfection with influenza and BCG in the lung led to exacerbation of the pulmonary disease and, in contrast to models in which influenza and BCG infection occurred in separate organs (44), resulted in delayed clearance of BCG. Although influenzamediated mechanisms affecting innate immunity may influence mycobacterial clearance from the lungs, both CD4 and CD8 T cells are required for effective control of BCG infections (45).…”
Section: Discussionmentioning
confidence: 98%